Evaluation of blood glucose-lowering activity of aqueous extract of bark of Ficus lacor Buch Ham in alloxan-induced diabetes in New Zealand white rabbits - Piyushkumar Mansinh Pargi; Manish Barvaliya; Bhargav Purohit (Medical Laboratory Journal)
Background: Although the anti-diabetic effects of various Ficus species have been investigated in animal models, research on the blood glucose-lowering potentials of Ficus lacor Buch Ham bark remains sparse. This study evaluated the blood glucose-lowering potentials of an aqueous extract derived from Ficus labor bark in a diabetic rabbit model. Methods: Diabetes was induced in rabbits through intravenous administration of alloxan monohydrate (120 mg/kg). 36 rabbits were divided into six groups, each consisting of six animals. Control groups included a non-diabetic control (Distilled water) and a diabetic control (Distilled water). Two experimental groups received Ficus lacor extract at doses of 100 mg/kg (Low-dose) and 200 mg/kg (High-dose) orally for six weeks. Metformin was used as an active control. A non-diabetic group (Extract control) was also administered Ficus lacor extract at 200 mg/kg. Fasting blood sugar (FBS) and post-prandial blood sugar (PP2BS) levels were measured weekly over the 6 weeks. The percentage reduction in blood glucose levels was calculated and compared for each group. Results: The administration of both low-dose and high-dose Ficus lacor extracts resulted in significant reductions in FBS and PP2BS levels in diabetic rabbits. After six weeks, the low-dose extract group exhibited an average reduction of 38.3% in FBS and 40.5% in PP2BS, whereas the high-dose extract group showed average reductions of 35.3% in FBS and 36.3% in PP2BS. Conclusion: The aqueous extract of Ficus lacor bark demonstrates substantial glucose-lowering activity, indicating its potential utility as a therapeutic agent in diabetes management.